Aggressive tax planning: The impact of profitability and Environment Social Governance (ESG) - Alfita Rakhmayani; Maya Aresteria; Deddy Sulestiyono; Fahma Indriawati (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to determine whether ESG (Environmental, Social, and Governance) scores can reduce or weaken the influence of profitability on tax planning. The data used in this study are secondary data obtained from Bloomberg and the Indonesia Stock Exchange (IDX) as of December 31, 2023. The research population includes all companies listed on the IDX in 2023, while the research sample consists of companies that meet specific criteria. Moderation regression analysis was conducted to address the research questions. The results indicate that both profitability and ESG scores have a positive effect on aggressive tax planning. However, ESG scores do not moderate the relationship between profitability and aggressive tax planning. This suggests that companies with high ESG implementation do not necessarily avoid aggressive tax planning practices.